2017
DOI: 10.1016/j.combustflame.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of a turbulent spray flame using Large Eddy Simulation with a stochastic breakup model

Abstract: A computational investigation of a turbulent methanol/air spray flame in which a poly-dispersed droplet distribution is achieved through the use of a pressure-swirl atomiser (also known as a simplex atomiser) is presented. A previously formulated stochastic approach towards the modelling of the breakup of droplets in the context of Large Eddy Simulation (LES) is extended to simulate methanol/air flames arising from simplex atomisers. Such atomisers are frequently used to deliver fine droplet distributions in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 81 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…Additional unclosed terms in the mass conservation equation are thus prevented. Further details on the filtered governing equations of mass, momentum and scalars with liquid-phase source terms can be found in [26,30]. The unknown contribution to the filtered chemical source term (ρω α ) is taken into account using a joint sub-grid scale pdf for all the scalar variables required to describe chemical reaction as proposed in [32].…”
Section: Gas-phase Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional unclosed terms in the mass conservation equation are thus prevented. Further details on the filtered governing equations of mass, momentum and scalars with liquid-phase source terms can be found in [26,30]. The unknown contribution to the filtered chemical source term (ρω α ) is taken into account using a joint sub-grid scale pdf for all the scalar variables required to describe chemical reaction as proposed in [32].…”
Section: Gas-phase Governing Equationsmentioning
confidence: 99%
“…It is necessary only that the random variable has a mean of zero and standard deviation of unity so providing this property is maintained; the choice of distribution is of little consequence. The formulation has been used successfully over various spray flames in the past -for example, [30]. The solutions of Eq.…”
Section: Eulerian Monte Carlo Field Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous scholars have conducted in-depth theoretical and experimental studies on this issue, and found that the spray cone angle has a decisive influence on the spray THERMAL SCIENCE: Year 2020, Vol. 24 liquid's flow rates [3], the droplet size distribution [4], the final flame shape [5], and temperature characteristics [6][7][8][9]. It is generally accepted that, with an increase in the spray cone angle at the same flow rate, the spray penetration distance decreases and the flame becomes wider and shorter.…”
Section: Introductionmentioning
confidence: 99%
“…Large eddy simulations (LES) of atomizing spray were reported by Apte et al [13], Jones and Lettieri [14], Irannejad et al [15], Jones et al [16], Khan et al [17] and Noh et al [18]. Li et al [19] performed Large-Eddy simulations of ethanol spray combustion.…”
Section: Introductionmentioning
confidence: 99%